Maternal Microbe-Specific Modulation of Inflammatory Response in Extremely Low-Gestational-Age Newborns - Raina N. Fichorova (American Society for Microbiology, 2011)
ABSTRACT The fetal response to intrauterine inflammatory stimuli appears to contribute to the onset of preterm labor as well as fetal injury, especially affecting newborns of extremely low gestational age. To investigate the role of placental colonization by specific groups of microorganisms in the development of inflammatory responses present at birth, we analyzed 25 protein biomarkers in dry blood spots obtained from 527 newborns delivered by Caesarean section in the 23rd to 27th gestation weeks. Bacteria were detected in placentas and characterized by culture techniques. Odds ratios for having protein concentrations in the top quartile for gestation age for individual and groups of microorganisms were calculated. Mixed bacterial vaginosis (BV) organisms were associated with a proinflammatory pattern similar to those of infectious facultative anaerobes. Prevotella and Gardnerella species, anaerobic streptococci, peptostreptococci, and genital mycoplasmas each appeared to be associated with a different pattern of elevated blood levels of inflammation-related proteins. Lactobacillus was associated with low odds of an inflammatory response. This study provides evidence that microorganisms colonizing the placenta provoke distinctive newborn inflammatory responses and that Lactobacillus may suppress these responses. IMPORTANCE Despite improved intensive care, preterm and especially extremely low-gestation-age neonates continue to be at a considerably increased risk of morbidity, mortality, and developmental problems. The fetal inflammatory response appears to contribute to the onset of preterm labor, fetal injury, and complications, underlying lifetime health challenges facing these children. This study provides evidence that bacterial colonization of the very preterm placenta is associated with distinct microorganism-specific inflammatory protein profiles in the newborn blood specimens. We also provide evidence that Lactobacillus reduces inflammatory responses in newborns. Our data support the concept that targeting of placental colonization by specific drugs or probiotics during early pregnancy holds promise for preventing not only preterm birth but also subsequent and long-lasting, inflammation-provoked late sequelae.